2020
DOI: 10.3389/fnhum.2020.00077
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Auricular Vagus Nerve Stimulation-Paired Rehabilitation for Oromotor Feeding Problems in Newborns: An Open-Label Pilot Study

Abstract: Neonates born premature or who suffer brain injury at birth often have oral feeding dysfunction and do not meet oral intake requirements needed for discharge. Low oral intake volumes result in extended stays in the hospital (>2 months) and can lead to surgical implant and explant of a gastrostomy tube (G-tube). Prior work suggests pairing vagus nerve stimulation (VNS) with motor activity accelerates functional improvements after stroke, and transcutaneous auricular VNS (taVNS) has emerged as promising noninvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…However, in an effort allocation task, concurrent tVNS increased participants' drive to obtain lesswanted prospective food rewards (Neuser et al, 2020). Two weeks of tVNS concurrent with bottle-feeding improved oral intake in about half of premature or brain injured infants who had failed oral feeding until that time (Badran et al, 2020). These results suggest that concurrent tVNS may affect hedonic responses to orally sampled foods and food intake, which has not been examined to our awareness.…”
Section: Introductionmentioning
confidence: 81%
“…However, in an effort allocation task, concurrent tVNS increased participants' drive to obtain lesswanted prospective food rewards (Neuser et al, 2020). Two weeks of tVNS concurrent with bottle-feeding improved oral intake in about half of premature or brain injured infants who had failed oral feeding until that time (Badran et al, 2020). These results suggest that concurrent tVNS may affect hedonic responses to orally sampled foods and food intake, which has not been examined to our awareness.…”
Section: Introductionmentioning
confidence: 81%
“…A pilot study of tVNS in schizophrenia found no effect on symptom severity (Hasan et al, 2015 ). Moreover, many potential targets for treatment via tVNS have been suggested, including attention deficit hyperactivity disorder (ADHD) (Beste et al, 2016 ), autism spectrum disorders (Jin and Kong, 2016 ), Alzheimer's dementia (Jacobs et al, 2015 ), post-operative cognitive dysfunction (Xiong et al, 2009 ), increased risk of type II diabetes (Huang et al, 2014 ), preterm infants with oromotor dysfunction (Badran et al, 2020 ), chronic stroke patients (Capone et al, 2017 ), coronary insufficiency (Afanasiev et al, 2016 ) and chronic migraine (Straube et al, 2015 ). The idea that tVNS might be a promising treatment in Alzheimer's dementia has received support through recent evidence that tVNS can recover impaired microglia function in a mouse model of Alzheimer's dementia (Kaczmarczyk et al, 2017 ; Huffman et al, 2019 ), and there is an ongoing clinical trial of tVNS as a treatment for mild cognitive impairment (NCT03359902).…”
Section: Modes Of Applicationmentioning
confidence: 99%
“…MAAVNS, however, pairs taVNS with motor activity, using 500 µs pulses at 25 Hz that are turned on during the duration of a targeted motor activity (Cook et al, 2020b). MAAVNS has been demonstrated to be a promising neurorehabiltiation tool (Badran et al, 2018c(Badran et al, , 2020 and in early studies has demonstrated promise in facilitating motor learning in neonates MAAVNS is further continued to be explored in adult post-stroke rehabilitation trials.…”
Section: Tavns Human Clinical Trialsmentioning
confidence: 99%